PEMODELAN BANGKITAN DARI PERUMAHAN MENGGUNAKAN ANALISA REGRESI DAN ARTIFICIAL NEURAL NETWORK (Studi Kasus Di Kecamatan Banyuasin I) - Muizzi, Lukman (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2018)
With the growing population means progressneed housing development. Urban sprawl that is not followed by infrastructure development could result in problems, one of which is the problem of transportation. Transportation problem is the impact of the interaction between land use, network systems and movement. The lack of balance from one of these systems cause a transportation problem, one of which is traffic congestion.This study aims to model the rise of movements performed by a community of several types of housing in the Village District of Mariana and Mariana Banyuasin Ilir I. The study was conducted to determine and estimate the magnitude of the movement that came out of the housing so that forecasting will be done to anticipate problems that will occur in the future.Analysis of trip generation is done by regression methods and methods of Artificial Neural Network (ANN). From the calculation results can be concluded that a variable number of families (X1) and a large income (X4) has an important role for the model compared with the amount of car ownership variable (X2) and motorcycle (X3). The combination of variables X1 and X4 using ANN method produces rates R2 = 0.952, so it was chosen as the model of trip generation and Mariana Mariana Ilir Urban Village District Banyuasin I.